ANALISIS SWOT PADA UMKM (BASO ACI) - Husni Fauzi Ramadhan; Tyna Yunita, Ivan Ardiansyah, Rizky Maulana (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
At present the development of business life which is increasingly advanced and fast, is a challenge or at the same time a threat for entrepreneurs to maintain their profitability, support the progress of their business and win the competition with other businesses. In the field of the food industry is one of several forms of business or business that is very fast in demand among business people today. The development of the culinary business in Indonesia in this modern era is growing rapidly where various delicious dishes have been developed. Micro, small and medium enterprises (MSMEs) are one of the main pillars of the country's economic development and can prove their resilience in the face of economic crises. In order to survive and compete with other similar businesses, research was conducted to analyze existing internal and external environmental factors so that appropriate strategies could be determined. This research is descriptive in nature and data collection techniques are carried out by means of observation, interviews, and questionnaires. Data analysis using SWOT analysis. This analysis pays attention to internal factors (Strengths and Weaknesses) and external factors (Opportunities and Threats).